Organizational change: The challenge of change aversion - Jason A. Hubbart (Administrative Sciences, 2023)
Organizational change has been investigated for decades, with many works addressing change adoption challenges. Change aversion, like change resistance, is not uncommon, but going unchecked can reduce organizational change initiative success. This communication aims to provide a concise in-road for students and practitioners to the organizational change and change aversion literature. An attempt is made to enter this complicated discussion in a way that may assist the reader in understanding what change aversion is, how vital acceptance of organizational change is, and that there are operational practices that can facilitate a culture of change acceptance. Aversion to change may result from many factors, including (but not limited to) fear of the unknown, discomfort over a potential loss of control, and the instinctive tendency to prefer the familiar over the unfamiliar. However, despite advancements in the administration of inevitable organizational change moments, challenges related to change resistance can always occur, particularly lacking effective change leadership. Leadership can address resistance early, thus more readily guaranteeing a positive and productive organizational change outcome. Offering employees quality jobs and an inclusive, empathetic, and considerate environment can lead to early organizational buy-in and change acceptance, thereby improving long-term organization efficiencies and outputs. Ultimately, organizational change initiatives are most likely to succeed with buy-in and acceptance, thereby enabling businesses to remain competitive in a continuously evolving environment.
Keywords: 350; change aversion; employee inclusivity; employee positioning; leadership; management; organizational advancement; organizational change; resistance to change